If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -13 = -8m + -14 Reorder the terms: -13 + 2m = -8m + -14 Reorder the terms: -13 + 2m = -14 + -8m Solving -13 + 2m = -14 + -8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '8m' to each side of the equation. -13 + 2m + 8m = -14 + -8m + 8m Combine like terms: 2m + 8m = 10m -13 + 10m = -14 + -8m + 8m Combine like terms: -8m + 8m = 0 -13 + 10m = -14 + 0 -13 + 10m = -14 Add '13' to each side of the equation. -13 + 13 + 10m = -14 + 13 Combine like terms: -13 + 13 = 0 0 + 10m = -14 + 13 10m = -14 + 13 Combine like terms: -14 + 13 = -1 10m = -1 Divide each side by '10'. m = -0.1 Simplifying m = -0.1
| 19x-19=11x-11 | | 2(x+6)=2+12x | | 2x+6(2x-11)=60 | | 4b+8=56 | | 4a+4h-2=0 | | (1/8)^-2 | | 4=w+2 | | 177=7x+2(4x+6) | | 7.18-1.98= | | 2x^2-16x+36=0 | | abs(5x-1)=8 | | 8x-15=6x+11 | | 7-3r=r-4(2+n) | | y-60=-17/2(x-20) | | 5x-37=11+2x | | 4x-6(3x-14)=-14 | | 3=1.25x | | -13/10w | | 2y^2-y=6 | | 7.2=4z+3p-3z | | -2x+7(-x-4)=-118 | | -6(2x+7)=22+4x | | 6(v-6)=3v-21 | | 10+0.07(15x)+9x=15x | | 3+n+5= | | 8x-15=3x+11 | | 3+5x=2x+3 | | 10x+17=-143+2x | | 16-4n=-n | | 6n+4=-18n | | y+7=-14 | | 4x-12=12-6x |